2013
DOI: 10.1074/jbc.m113.514521
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Substrate Conversion in a New Aromatic Peroxygenase

Abstract: Background: Aromatic peroxygenases (APOs) are the "missing link" between heme peroxidases and P450-monooxygenases. Results: Based on two crystal structures the substrate conversion of APOs is elucidated. Conclusion:The specific design of the heme cavity and the distal heme access channel govern substrate specificity. Significance: APOs can be utilized in biotechnology and organic synthesis having significant advantages when compared with cytochrome P450 enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 128 publications
(143 citation statements)
references
References 54 publications
7
135
0
1
Order By: Relevance
“…S. cerevisiae tends to hyperglycosylate foreign proteins up to levels of ϳ50%, conferring on them increased stability and protection against proteolytic degradation. The glycosylation of wt UPO1 observed was exclusively dependent on 6 predicted N-glycosylation sites (Oglycosylation sites are not described for the enzyme), associated with up to 8 moieties of the high-mannose type (30,35). None of the amino acid substitutions in PaDa-I introduced new glycosylation motifs, and thus, the higher sugar content in the mutant may be due to an increased Golgi residence time that leads to the addition of more mannose moieties, as described in other directedevolution studies in yeast (14,17).…”
Section: Resultsmentioning
confidence: 98%
“…S. cerevisiae tends to hyperglycosylate foreign proteins up to levels of ϳ50%, conferring on them increased stability and protection against proteolytic degradation. The glycosylation of wt UPO1 observed was exclusively dependent on 6 predicted N-glycosylation sites (Oglycosylation sites are not described for the enzyme), associated with up to 8 moieties of the high-mannose type (30,35). None of the amino acid substitutions in PaDa-I introduced new glycosylation motifs, and thus, the higher sugar content in the mutant may be due to an increased Golgi residence time that leads to the addition of more mannose moieties, as described in other directedevolution studies in yeast (14,17).…”
Section: Resultsmentioning
confidence: 98%
“…[26] Thus, we examined the recent AaeUPO1 crystal structure to find a means to suppress alternative peroxidative pathways. [27] QM/MM calculations identified Trp24 as the highest oxidizable surface residue (see computational analysis below); hence, we constructed site-directed variants using the PaDa-I and JaWa variants as templates. The corresponding PaDa-I-W24F and JaWa-W24F mutants were compared: Irrespective of the variant and the reducing substrate tested, the W24F mutation decreased the peroxidative activity by ~60% ( Figure 3B).…”
Section: Biochemical Characterizationmentioning
confidence: 99%
“…The structure of wild-type UPO1 (purified from A. aegerita culture) at a resolution of 2.1 Å (Protein Data Bank Europe [PDB] accession number 2YOR) was used as departure point for PaDa-I and JaWa variants modeling. [27] The wild-type UPO1 crystal was used. Five different mutations (V57A-L67F-V75I-I248V-F311L) were introduced to model PaDa-I variant, with two additional mutations (G241D-R257K) for JaWa.…”
Section: Computational Analysismentioning
confidence: 99%
“…Accordingly, we anticipated that these water-soluble nitroxyl radicals might be able to reduce APO-I readily but would not reduce APO-II efficiently. Furthermore, since cyclohexane carboxylic acid was found to be an excellent substrate for APO (29), the similar molecular topographies of 4-carboxy-TEMPO and 3-carboxy-PROXYL suggested that they would fit into the relatively small, conical active site of APO (25). We tested the reaction of 3-carboxy-PROXYL with the well-studied enzyme CPO in a single-turnover experiment.…”
Section: Significancementioning
confidence: 99%
“…These proteins are unrelated to CYP enzymes, according to their amino acid sequences, and are only distantly related to CPO, with about 30% sequence similarity and a similar tertiary structure (25). APO proteins have shown high activity for the oxygenation of aliphatic and aromatic hydrocarbons and a variety of other organic substrates, in sharp contrast to CPO (26).…”
mentioning
confidence: 99%